Pengaruh Experiential Marketing terhadap Minat Pembelian Ulang melalui Kepuasan Konsumen sebagai Variabel Intervening - Isnain Kharolina; Ralina Transistari (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2021)
This study aims to analyze the effect of experiential marketing on consumer repurchase intention in a café, either directly or mediated by customer satisfaction. Sampling with non probability sampling method using purposive sampling technique. The number of respondents as many as 135 people who are consumers of Cafe MJ in Purwokerto. The data analysis method in this research is Path Analysis. The results showed that experiential marketing has a positive effect on customer satisfaction, experiential marketing has no effect on repurchase intention, customer satisfaction has a positive effect on repurchase intention, and experiential marketing has an indirect effect on repurchase intention through customer satisfaction.